Undisciplining the Museum: Indigenous Relationality as Religion - Mendoza, Rebecca J. (Religions, 2024)
What does it mean to decolonize or undiscipline the anthropology museum? What happens when the museum is confronted by Indigenous and descendant communities who demand an ethic of care rooted in relational ontologies and epistemologies? This article features Indigenous creativity as it has disrupted ‘business as usual’ in anthropology museums. This is primarily evidenced by Fork Peck Tribes who confronted the University of Montana to enact a long-overdue repatriation. Additional examples from The Metropolitan Museum of Art and Peabody Museum of Archaeology and Ethnology at Harvard demonstrate diverse expressions of relationality among Indigenous and descendant communities. These interventions are analyzed through Critical Indigenous Theory to specify the ways in which Indigenous religious traditions refuse the narratives and norms of settler colonial knowledge production and undermine the imperial museological practices of preservation. Instead, relationality is prioritized in the caretaking of and connection with more-than-human entities and materials in the museum. This article emphasizes relationality and repatriation as religious acts that challenge assumptions embedded in imperial and settler colonial approaches to history and science. From various social locations and through multiple strategies, we see the active undisciplining of the museum by Indigenous and descendant communities.